2013
DOI: 10.1095/biolreprod.113.108571
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine Inhibits Decidualization of Human Endometrial Stromal Cells and Decreases Litter Sizes in Mice1

Abstract: Embryo implantation in the uterus depends on decidualization of the endometrial stromal cells (ESCs), and glucose utilization via the pentose phosphate pathway is critical in this process. We hypothesized that the amino sugar glucosamine may block the pentose phosphate pathway via inhibition of the rate-limiting enzyme glucose-6-phosphate dehydrogenase in ESCs and therefore impair decidualization and embryo implantation, thus preventing pregnancy. Both human primary and immortalized ESCs were decidualized in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…In contrast, several studies demonstrated an inhibitory effect of GlcN on litter size and embryo development. Tsai et al [25] reported that litter size decreased when a sustained-release GlcN (15, 150 or 1500 μg) was implanted into uterine horn ten days before coitus and during pregnancy compared with that in the placebo-implanted control group. Further, deteriorated implantation and reduced litter size on day 18 of gestation have been reported when 8-weekold mice were injected intraperitoneally with 20 or 400 mg/ kg GlcN during periconception [26].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several studies demonstrated an inhibitory effect of GlcN on litter size and embryo development. Tsai et al [25] reported that litter size decreased when a sustained-release GlcN (15, 150 or 1500 μg) was implanted into uterine horn ten days before coitus and during pregnancy compared with that in the placebo-implanted control group. Further, deteriorated implantation and reduced litter size on day 18 of gestation have been reported when 8-weekold mice were injected intraperitoneally with 20 or 400 mg/ kg GlcN during periconception [26].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, decidualization is required for successful embryo implantation and establishment of pregnancy in human (Tsai et al, 2013). Thus, inappropriate differentiation or a decreased number of stromal cells undergoing decidualization may lead to implantation failure.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly there appeared to be an age dependency to different outcomes with reduced litter size independent of dose in younger mothers compared with a significantly higher incidence of fetal congenital abnormalities in older mothers, similar to and consistent with pathologies associated with hyperglycemic or diabetic mice (Schelbach et al 2013). It is difficult to know the relevant contribution of effects on embryonic development versus maternal perturbations, given that maternal systemic glucosamine supplementation may also impact on decidualisation (Tsai et al 2013) and by implication subsequent placentation to contribute to altered fetal growth in response to an adverse environment.…”
Section: Periconceptional Hsp Pertubation and Postnatal Outcomesmentioning
confidence: 95%